Development of Science Assessment to Measure Creative Thinking Ability of Seventh-grade Junior High School Students - Redo Akbar; Ahmad Walid; Kasmantoni Kasmantoni (Fakultas Tarbiyah dan Ilmu Keguruan, UIN Kiai Haji Achmad Siddiq Jember, 2022)
This study has purposes which to determine the development of creative thinking assessments on the topic of the interaction between living things and their environment and to describe the feasibility and effectiveness of developing creative thinking assessments on the topic of the interaction between living things and their environment. The type of research used is Research and Development with a quantitative approach. The results showed that the development of creative thinking assessment on the topic of the interaction living things and their environment using the Borg and Gall development model which consists of eight steps, and the feasibility of this development product was tested by 3 lecturers, namely: 1 lecturer as an assessment expert, 1 lecturer as language, and 1 material expert. Based on the results of the validation assessment, feasibility of assessment was 81.5%, language validation was 88.8%, and content validation was 94.4%. Furthermore, it can be concluded that the development of creative thinking assessment on the topic of the interaction of living things and their environment is included in the criteria that are very suitable to be used without any revision.